Demonstration of neutron identification in neutrino interactions in the MicroBooNE liquid argon time projection chamber - The MicroBooNE Collaboration; P. Abratenko; O. Alterkait; D. Andrade Aldana; L. Arellano; J. Asaadi; A. Ashkenazi; S. Balasubramanian; B. Baller; A. Barnard; G. Barr; D. Barrow; et al. (European Physical Journal C: Particles and Fields)
Abstract A significant challenge in measurements of neutrino oscillations is reconstructing the incoming neutrino energies. While modern fully-active tracking calorimeters such as liquid argon time projection chambers in principle allow the measurement of all final state particles above some detection threshold, undetected neutrons remain a considerable source of missing energy with little to no data constraining their production rates and kinematics. We present the first demonstration of tagging neutrino-induced neutrons in liquid argon time projection chambers using secondary protons emitted from neutron-argon interactions in the MicroBooNE detector. We describe the method developed to identify neutrino-induced neutrons and demonstrate its performance using neutrons produced in muon-neutrino charged current interactions. The method is validated using a small subset of MicroBooNE’s total dataset. The selection yields a sample with $$60%$$ 60 % of selected tracks corresponding to neutron-induced secondary protons. At this purity, the integrated efficiency is 8.4% for neutrons that produce a detectable proton.